Using STORM and TIRF in tandem to investigate adherence and migration patterns in stem cells - Matyesini, Sandisiwe Manyathi-Mankwali (Stellenbosch : Stellenbosch University, 2021)
Thesis (MMed)--Stellenbosch University, 2021.